Scaling up syngas production with controllable H2/CO ratio in a highly efficient, compact, and durable solid oxide coelectrolysis cell unit-bundle. (1st January 2020) - Lee, Dong-Young; Mehran, Muhammad Taqi; Kim, Jonghwan; Kim, Sangcho; Lee, Seung-Bok; Song, Rak-Hyun; Ko, Eun-Yong; Hong, Jong-Eun; Huh, Joo-Youl; Lim, Tak-Hyoung
Graphical abstract: Highlights: Highly efficient, durable and modular SOC cells and stacks developed. Controllable syngas H2 /CO ratio achieved between 1 and 4 with 90% CO2 conversion. A maximum current density of −3.2A/cm 2 at 1.6 V at 800 °C was achieved. Abstract: High-temperature coelectrolysis of H2 O and CO2 by using solid oxide coelectrolysis cells (SOC) is considered to be among the most efficient processes for CO2 conversion as these SOCs can efficiently utilize both heat and renewable electrical energy. One of the key components is the development of highly efficient, modular SOC cells and stacks to further scale up the CO2 conversion process towards industrial applications. In this study, we developed highly efficient and durable flat-tubular solid oxide coelectrolysis cells (FT-SOCs) and investigated the electrochemical performance (I-V, EIS, long-term galvanostatic test) of single cells and a 6-cell bundle for CO2 -H2 O coelectrolysis to produce syngas with controllable H2 /CO ratios. The FT-SOC with an active area of 40 cm 2 reached a maximum current density of −3.2A/cm 2 at 1.6 V at 800 °C and an H2 O/CO2 ratio of 2. In the 6-cell FT-SOC bundle, 90% CO2 conversion was achieved by producing high-quality syngas with flexible H2 /CO ratios and stable long-term operation for continuous 500 h. The results of this study show that by using an FT-SOC bundle, scalable and controllable syngas quality could be produced and integrated with the multitude of downstream processes.